PENGARUH ATRIBUT SUPERMARKET TERHADAP MOTIF BELANJA HEDONIK MOTIF BELANJA UTILITARIAN DAN LOYALITAS KONSUMEN - Hartono Subagio (Jurnal Manajemen Pemasaran, 2011)
Attributes Supermarket stimulate the motive shopper to buying product, the motive Consuming and buying motives are classified into Hedonic and utilitarian. The fulfilness of hedonic and utilitarian motives lead to shoppers’ loyalty to the supermarket. The purpose of the study is to review the theory of Stimulus Organism Response addressed by MehrabianRussel, the concept of shopping motive developed by Baker and Donovan, and the concept of motive shopping Hedonic by Arnold Reynold. It was Empirical study on Big Supermarket in Surabaya.The Human behavior response and perceptionalanswers as well as concerned with inter variable effects through hypothesis tests by means of SEM analysis. The maximum likelihood estimation was derived from 200 respondents. The result s of the study showed that atribute supermarket significanly affected motive Hedonic and motive Utilitarian and loyalty. The empirical findings from the study showed to motive Hedonic morestrongth impact than motive utilitarian.